ECONOMIC ANALYSIS OF A COMPLEX PIG FARM - Tóth, Sándor; Nábrádi, András (Applied Studies in Agribusiness and Commerce, 2025)
The objective of this study is, beyond presenting the production and economic indicators of a complex pig farm established as a brownfield investment, to analyze its cost-income and profitability relations. The Authors conducted their calculations based on primary data collection and a preliminary calculation model. The technological equipment of the presented pig farm is competitive at the European level, and its production indicators also show favorable results. The capital investment demonstrates adequate profitability, as the internal rate of return (IRR) is 12.35%, while the net present value (NPV) of the investment at the end of the 15th year is HUF 1.36 billion. According to the model, the results indicate that, on the one hand, the investment is capital-intensive, but at the same time, large-scale livestock farms equipped with similarly advanced technology are definitely necessary, as they greatly contribute to improving the sector’s efficiency. There is further potential for achieving competitive advantages through increasing economies of scale. Appropriate human resources with the necessary expertise, genetics, and feeding must accompany the technological advancement.